ASPEK PIDANA DALAM PELAKSANAAN ISI COVERNOTE OLEH NOTARIS/PPAT DI KABUPATEN SLEMAN - , Puteri Prajaningrum Nurendra; , Prof. Dr. Edward Omar Sharif Hiariej, S.H., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research resolves the issue of Covernotes that have recently become popular due to the misunderstanding of different parties regarding the nature of Covernotes causing Notaries who issue them to be entangled in criminal matters. As a normative legal research supported by empiric data, 2 issues are being inspected. These are the misuse of the position of the Notary in the process of issuing a Covernote and the disavowal of the contents done by the Notary resulting to criminal offense. The purpose of this research is to present clearly the process of issuing a Covernote according to the office code of ethics principles, and to give clarity on the forms of disavowal of the contents of Covernotes resulting to criminal offense. The research finding shows that many parties still hold the Covernote as a deed/ certificate, whereas Covernotes are in truth only valid as reference letters that do not have the strength of exact verification, similar to an ambtelijk acte. Principally, the contents of a Covernote ony states the ability to finish a process and hand over the result to the eligible party. There is no standardized form of a Covernote. In the practice, to keep the Banks well-being safe, the Bank often standardizes the contents. If not dealt with properly, this can trap the Notary. The disavowal of the contents of a Covernote is caused by external factors that occur due to the encouragement of the clients that result to the violation of the law, and internal factors caused by the impulse of the Notary them self. This criminal offense leads to forgery that inflicts loss (Article 263 KUHP), and embezzlement that occurs during their duty and responsilbility as public officials, therefore categorizing as embezzlement with incriminating elements (Article 374 KUHP).